Effects of ph and ionic strength on the protease activity of gastric extracts from the coho salmon oncorhynchus kisutch - Marquez, Lorenzo (2019)
The activity of fish acid proteases is strongly dependent on the pH, and many basic and applied works had focused on researching the pH-profile of digestive proteases using different buffered media. Nevertheless, enzymatic activity is also known to be affected by the ionic strength (IS) of the medium. The present work is aimed at researching the combined effects of pH (2.5, 3.0, 3.5, 3.75 and 4.0) and IS (50, 100 and 200 mM) on the protease activity of gastric extracts of juvenile Coho salmon Oncorhynchus kisutch. It is concluded that the activity of Coho salmon gastric proteases is maximal at pH 2.5-3.0, drops towards pH 4.0 irrespective of ionic strength, and they showed a lower activity at IS 50 mM in comparison to IS 100 or 200 mM. The present results point out to the convenience of considering the effect of ionic strength when measuring the activity of fish gastric proteases.